Hydrogen gas detection via photothermal deflection measurement - Kalli, Kyriacos; Othonos, Andreas S.; Christofidès, Constantinos (My University, 1997)
A study of a thermal wave hydrogen sensor interrogated via transverse optical beam deflection spectroscopy is presented. The sensor is a thin film polyvinylidene fluoride film coated with a thin palladium layer. The sensitivity to hydrogen results from thermal boundary condition changes at the gas-film interface and depends upon the thermophysical properties of the gas. A simple one-dimensional model is developed to qualitatively and semi-quantitatively describe the experimental results and it shows good agreement with the experiment. Concentrations of 0.1% hydrogen in the presence of a balanced air mixture and at room temperature were measured for this sensor and they indicate possible sensitivities approaching 100 ppm.
Keywords: Spectroscopy; Hydrogen; Thin films; Gas